REGULATION OF LEGAL LABOUR MIGRATION FROM THIRD COUNTRIES UNDER EU LAW - G. Martirosyan, Diana (Revista Gênero e Interdisciplinaridade, 2020)
The article considers the EU legislation regulating legal labour migration from third countries, which has lately become one of the most pressing issues in the European Union. In particular, the authors consider provisions of the EU/EC Directives and cases of the Court of Justice of the European Union. They come to the conclusion that the EU institutions and bodies should take more careful approach to labour market needs, taking into account the necessary qualifications of workers. Under the current conditions of the European migrant crisis, the EU should further develop legal regulation of the general migration policy, with a particular attention to labour migration. It is necessary to establish and improve the incentives for migrants to study European languages, contributing to their integration in the EU member states. There is also a demand for the development of interactive tools helping potential migrant workers from third countries, which could be similar, for example, to the existing European job mobility portal EURES